PENGARUH PELATIHAN KEARSIPAN TERHADAP KINERJA TENAGA ADMINISTRASI DI PUSKESMAS PAGESANGAN - Kadek Dwipa Citra Lestari; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
This study aims to analyze the influence of archival training on improving the performance of administrative staff in Community Health Centers (Puskesmas) using the library research method. The main focus of this research is to evaluate how human resource competency development can address increasingly complex document management challenges, especially with the transition to the e-Puskesmas digital system. Secondary data were obtained from reputable scientific journal articles published within the last ten years. The analysis results from various literatures indicate a positive and significant correlation between the implementation of archival training and employee work productivity. Structured training has proven effective in transforming manual work patterns into more systematic ones, thereby minimizing data input errors and accelerating the retrieval time of medical information. These findings emphasize that the success of digital transformation at the Pagesangan Health Center does not only rely on technological sophistication but is heavily determined by the technical readiness of its employees. Although electronic systems can overcome physical storage space limitations, operational effectiveness still demands the ability of staff to manage databases accurately. Therefore, the synergy between modern technology and sustainable archival training is an absolute solution to ensure administrative order and professional health service quality. This research recommends the necessity of continuous human resource competency development policies for health administrative personnel.